Preventive chemotherapy in one year reduces by over 80% the number of individuals with Soil Transmitted Helminthiases causing morbidity. Results from meta-analysis - Marocco, Chiara (Trans R Soc Trop Med Hyg, 2017)
The morbidity due to Ascaris lumbricoides and Trichuris trichiura is caused by infections of moderate and heavy intensity while hookworm infections of all intensities are recognized to cause morbidity. This study aims to evaluate the effect of repeated round of preventive chemotherapy on the proportion of Soil Transmitted Helminth (STH) infections causing morbidity. We identified studies from 17 countries, reporting changes in the proportion of STH infection causing morbidity between baseline and follow up. In the studies identified, the average proportion of individuals with STH infections of moderate and heavy intensity was of 14% at baseline and was on average reduced to 2% by the intervention (i.e. 85% reduction). There was an average reduction of 73% after the first year of treatment, which reached almost 80% after 5 years and over 95% in 10 years of deworming interventions. The reduction in hookworm prevalence was 57% after 12 months reaching 78% after 5 years. We consider the results presented in this study especially useful for decision makers as it demonstrates the effectiveness of Preventive Chemotherapy in reducing STH prevalence and morbidity. We encourage the implementation of deworming programs to achieve the goal, set for 2020, to eliminate STH morbidity in children.